Molecular Classification of Large B-Cell Lymphoma and High-Grade B-Cell Lymphoma Cases and Association with Outcomes in Morocco - Mahat Taybi; Zineb Khammar; Noufissa Alami Drideb; Rhizlane Berrady; Sanae Benmiloud; Laila Bouguennouch; Sanae Elfakir; Laila Tahiri; Mohammed Majdoub; Laila Chbani; Nawal Hammas (Hemato)
Background: High-grade B-cell lymphoma with c-MYC and BCL2 and/or BCL6 rearrangements (HGBL-DHL/THL) is a recently identified category in the most recent World Health Organization (WHO) classification. For all tumors displaying the appearance of diffuse large B-cell lymphoma (DLBCL) or high-grade B-cell lymphoma (HGBL), it is necessary to perform fluorescence in situ hybridization (FISH) in order to achieve an accurate diagnosis. The findings of FISH and immunohistochemistry (IHC) examinations from 50 DLBCL/HGBL samples obtained from Hassan II University Hospital in Fez/Morocco are reported. Methods: This retrospective study included 50 patients diagnosed with DLBCL/HGBL over a period of nine years (2013–2022) and treated with RCHOP chemotherapy protocol. All patients underwent a histological study followed by an immunohistochemical study to confirm the diagnosis and to classify patients according to cell of origin into non-GCB and GCB subtypes; then, a cytogenetic study using FISH was performed to classify patients according to the presence or absence of rearrangements in the c-MYC, BCL2 and BCL6 genes. A comparison was made between the molecular subtypes of DLBCL/HGBL in relation to clinicopathological features and outcomes. Results: Among the 50 cases studied in our population, we found 5 cases of HGBL with DLBCL morphology and 45 cases of DLBCL, which consisted of 13 cases (28.89%) of GCB subtype and 32 cases (71.11%) of non-GCB subtype based on the immunohistochemistry Hans algorithm. After FISH testing of all cases, we found three cases of double-hit lymphoma (DHL) and one case of triple-hit lymphoma (THL). Thus, HGBL-DHL/THL accounted for 8% of the cases. Furthermore, two cases were detected with only one rearrangement in the BCL2 gene and one case harboring a rearrangement in the BCL6 gene. DHL and THL patients and patients with a single rearrangement (BCL2 or BCL6) have a worse prognosis than patients with no rearrangement. Conclusions: DHL and THL are an aggressive entity of HGBL with poorer outcomes in comparison to DLBCL/HGBL NOS. First-line treatment with the RCHOP chemotherapy protocol may not be effective for all aggressive DLBCL cases. More targeted treatment is crucial for better patient outcomes.